Atividade espontânea e estimulação do inseto (T. molitor) - Fim Neto, Arnaldo [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The heart of the insect is essentially myogenic, in others words, electrical activity and spontaneous contractions are generated by their muscle cells. However, the nature of pacemaker activity is not yet fully elucidated. One aspect that deserves attention, beyond the pacemaker activity, is the amplitude of heart contractions of the insect. For this, it is necessary that the heart to be stimulated electrically to the frequency to be controlled. In the present work, it was developed a method of stimulation (preparation and instrumentation). The contractile activity of the heart of the insect remained regular when stimulated at frequencies lightly above the spontaneous frequency. To characterize excitability of the preparation the intensity-duration curve was determined

O coração do inseto é essencialmente miogênico, ou seja, atividade elétrica e contrações espontâneas são geradas pelas suas células musculares. Entretanto, a natureza da atividade marcapasso não está ainda totalmente elucidada. Um dos aspectos que merece atenção, além da atividade marcapasso, é a amplitude das contrações do coração do inseto. Para isso, torna-se necessário que o coração seja estimulado eletricamente para que a freqüência seja controlada. No presente trabalho foi desenvolvido um método de estimulação (preparação e instrumentação). A atividade contrátil do coração do inseto se manteve regular quando estimulado a frequências ligeiramente superiores à freqüência espontânea. Para caracterizar a excitabilidade da preparação a curva intensidade-duração foi determinada
Keywords: Estimulação elétrica; Inseto; Marcapasso; Bioeletricity; Electrical stimulation; Tubular heart